From component manufacturer to service provider : Case: Company X - Velic, Adel (My University, 2019)
This research identifies the best practices of servitization process (e.g. transition stages, change process, overcoming challenges and achieved benefits) and provides useful information on optimisation and creation of the maintenance service offering. The research is provided as an assignment for a case company operating in civil defence shelter industry which aims to expand its business from component manufacturer to a service provider. The study is entirely qualitative. The first research question examines what has to be changed inside the case company so that maintenance services can be provided to the customers. This is studied through a literature review of existing servitization theories and theme interviews with experts from three Finnish industrial companies. The second research question examines how to make the customers interested in the case company’s services. This is approached with structured questionnaires which are sent to three different customer segments: 1) potential residential building customers and property managers, 2) construction companies and end users, and 3) the existing customers. According to the findings of this research, the case company should take into close consideration the following entities when setting up the maintenance service business: 1) defining a service strategy, 2) building organisational structure, 3) transforming organisational culture, 4) creating optimal service offering, 5) managing service knowledge and communication, and 6) pursued benefits and possible success factors. Based on the results of the semi-structured interviews, potential new customers must be made aware of the need of civil shelter maintenance services and the case company should offer services which include 1) inspection of the current state of civil shelter, 2) individual inspections and repairs, 3) leak tests and maintenance activities, and 4) maintenance contracts and training. Lastly, it is found that the case company should consider different options when selling maintenance services to the customers, such as face-to-face type of sale, collaboration with different business partners and/or offering the services as part of larger service packages.
Keywords: Servitization, Maintenance Service, Service Strategy, Organisational Structure, Organisational Culture, Service Knowledge and Communication.; fi=Tuotantotalous|en=Industrial Management|; Master's Programme in Industrial Management